Avaliação físico-química e bacteriológica de peixes anchovados - Pombo, Cecilia Riscado (2007)
The process to obtain fish anchovies consist on the fermentation of the product in which microbiological and tissue enzimes act over proteins. There is a difficulty to standarlizate the product because of the nonexistence of official padrons to regulamentate the technological process. The aim of this study was avaliate the quality of fish anchovies comercialized through phisycal-chemical and bacteriological parameters and compare three differents technological process. The bacteriological analisys made were: colifornms, Enterococcus spp. and Escherichia coli enumerations, count and identification of Staphylococcus aureus and isolation ando identification of Salmonella spp.. The physical-chemical paremeter avaliated were: production of Total Volatile Base (N-TVB), determination of pH and salt (NaCl) quantification (%). The presence of biogenic amines were determinated by Thin Layer Cromatography (TLC) and the quantification of histamine was made by the fluorimetric method. In the comercialized products the values of pH were between 5,08 and 5,73 and the values of Activity of water (Aw) were between 0,70 and 0,75. The salt concentration (%) observed was beteween 9,78 and 17,50 %. Bacteriological results were saticfactory, using as reference the RDC nº12 legislation (BRASIL, 2001) to avaliatethe presence of Salmonella spp., E. coli and coliforms. Two samples had counts of S. aureus above the value stablished by that lagislation. The enumeration of Enterococcus spp. isn´t preview by RDC nº 12 and the results obtained suggests a relation between the presence of this bacteria and the formation of histamine. When the different thecnological process were avaliated was stablished a significant difference in the formation of histamine (p<0,05). Eschericia spp., Klebsiella spp., Proteus spp., Shiguella spp., Citrobacter spp. and Pseudomonas spp. were isolated., but there was no isolation of Salmonella spp. and Enterococcus spp. The salt percentual values vary between 15,65 and 18,87 % and no significant difference was stablished (p> 0,05). Aw and pH data have shown significant differences between the three processes (p<0,05) and obtain values between 0,71 and 0,75, and 5,54 and 5,93 respectively. The values of N- TVB vary between 15,1 and 62,1 mgN/100g. In conclusion, the formation of histamine in this product occours in concern concentrations for public health. The usual process used by the industry present better resoults acording to the physical-chemical analises even though had histamine formation that might produce sintimatology of intoxication on consumer. However, more studies are necessary.